Droning, zoning and organizing: Kafkaesque reflections on the nomos of the earth in the northwestern tribal belt of Pakistan - Nasir, Muhammad Ali (Space & polity, 2015)
This article reflects on the spatiality of the “War on Terror”. It argues that the “War on Terror” is a discourse that identifies the exceptional, i.e. terror, in order to normalize spaces and subjects. Since these standards (norm/ exception) presuppose an order, it relies on Schmitt’s concept of nomos in order to theorize how the spatial dynamics of the “War on Terror” are connected to an order that enables life and law to be shaped accordingly. The concept of nomos is read in tandem with Kafka’s concept of the wall, in order to tone down the aspects of decisiveness and totality associated with the concept of nomos. The empirical focus of the discussion is on the northwestern tribal belt of Pakistan.